Synthesis and investigation of the bimetallic nanoparticles prepared by redoxtransmetalation interaction - Auchynnikava, Elena A.; Vorobyova, Svetlana A.; Sohor, Alesya A. (Journal of the Belarusian State University. Chemistry, 2019)
Composite nanoparticles, containing copper, copper (I) oxide and silver, were prepared by redoxtransmetalation interaction of metallic copper and silver nitrate. The morphology and phase composition of the prepared nanoparticles were investigated by transmission electron microscopy (TEM) and powder Xray diffraction (XRD). The TEM investigation shows that discrete spherical silver nanoparticles with an average diameter of 15 nm are formed onto the surface of copper nanoparticles as a result of the redoxtransmetalation interaction of copper and silver nitrate. According to Xray data the prepared samples contain Cu, Cu2O, Ag and almost all amount of metallic copper are oxidized as a result of Ag+ reduction.